Pengaruh Fleksibilitas Akuntansi Dan Pengungkapan Laporan Keuangan Terhadap Real Earning Management - Boniface Ata Donatus; D Jefryan Christian Cabelen; Tri Ratnawati (Jurnal Riset Akuntansi, 2023)
This research purpose to examine influence of accounting flexibility, level of disclosure of financial statement and litigation risk to real earning management, this research also explore the role of audit quality to the relationship between accounting flexibility, level of disclosure of financial statement and litigation risk to real earning management. This research is done at the Indonesia Stock Exchange with population of 156 of manufacturing companies. The technical of sample taken by using the purposive sampling method, with 42 sample companies. The technique of data analysis use the SEM analysis with the aid of AMOS version 22. Result of this research show that accounting flexibility, level of disclosure of financial statement and litigation risk does not influence to real earning management, and also audit quality does not influence to the relationship between accounting flexibility, level of disclosure of financial statement and litigation risk to real earning management.